On form and function of politeness formulae - Schlund, Katrin (Journal of politeness research, 2014)
This paper focuses on the notion of politeness formulae in linguistic - politeness research. It argues that the formal make-up of politeness formulae - is crucially motivated by their function. The major claim of this paper is thus - that there is a link between form and function of expressions of linguistic politeness. - The usefulness of this account will be illustrated by the analysis of - empirical data from Slavic languages and German. Reference to Roman Jakobson’s - markedness theory will show that the choice of linguistic means is not - only dependent on concrete contexts (as is usually claimed in linguistic politeness - theory) but also motivated by the language system itself.